THE ROLE AND PLACE OF MULTILINGUALISM IN MODERN EDUCATION - Solovyyova, N.A.; Tanat, D. (PUBLISHINGS of Kostanay State Pedagogical University, 2017)
Language is the most alive, most plentiful and strong communication connecting the become obsolete, living and future generations of the people in one great, historical, alive, whole. Language – the life of people. In the country entering into the world community the favorable conditions for studying and distribution of languages are created. The multilingualism is an objective cultural and economic requirement. Now is recognized as training in languages as the priority direction education updating. In the message of the President to the people of Kazakhstan it is told: "Education reform is one of the major tols, allowing to provide actual competitiveness of Kazakhstan. We need the modern education system corresponding to requirements of economic and public modernization. Our main goal – to attract interest in studying of languages.Multilingualism – a way to the future".
Keywords: language; multilingualism; education